Partnership Governance as A Base for Strengthening Regional Tourism (Journal of Advanced Research in Social Sciences, 2019)
Batu City as a city that has a popular tourist destination also faced with this problem. Some tourist objects and attractions (ODTW) and cultural events have been carried out through cooperation between the three pillars of tourism, but until now still encounter various obstacles that are generally not based on partnership. Paper is downloading said the cooperation between the government and the private sector and the community at events travel "Stone Flower Festival" in Batu based on partnership. In this event developed the concept of a new partnership to be able to give a theoretical explanation of the phenomena associated with the implementation of regional tourism affairs. With the new concept of partnership, clarity is gained about the role of stakeholders, the policies developed by the government and the impacts on stakeholders. The developed partnership is equal and autonomous, sharing benefits and risks, pooling of resources, high intensity, and valid for a long period. By using qualitative research methods and using interview techniques, focus group discussions and observations, this study of tourism partnerships results in the finding that the roles of each stakeholder are in accordance with their capacities, policies taken by the Batu City Government have led to partnerships through sharing management and resources, and the impact of the partnership brings an increase in local own-source revenue and community income. Recommendations that can be submitted so that the Batu Flower Festival event can be continued and involve a wider community and more massive promotions.